PUBLIC PERCEPTIONS ABOUT THE FRUIT BATS IN TWO HORTICULTURALLY IMPORTANT DISTRICTS OF PAKISTAN - M. Mahmood-ul-Hassan; Faiz-ur-Rehman; M. Salim (Journal of Animal and Plant Sciences, 2011)
This study reflects the awareness level and public attitude towards bats in two northern districts of Pakistan that are important for their horticulture-based economy. A total of 225 persons were interviewed in Peshawar (n = 103) and Charsadda (n = 122) districts of the Khyber Pakhtunkhwa (KP). 100% of the respondents were unaware of the ecological services rendered by bats and reflected a negative attitude towards them.  They did neither like to eat them (99.6%) nor did they consider them to be hematophagous (blood sucking) (96.9%). Bats were of no use (98.7%) and were symbols of bad omen (78.2%). All of them (100%) refused to have bat roosts close to their house. There was a firm belief that bats feed solely on fruit, particularly persimmon Diospyros kaki (81.5%) and inflict heavy economic losses (43.8%). This aversive attitude is leading to unnecessary killing of the bats in the area and 16.4% of the respondents claim to have killed bats. Conservation education and non-consumptive wildlife-oriented tourism is needed to convince the people that superstitious beliefs and myths about the bats are baseless.
Keywords: Awareness; Conservation; Food; Fruit bats; Heamatophagy; Indian flying fox; Persimmon